Binder-jetting of TiCN-based cermets. (20th October 2022) - Berger, Christian; Pötschke, Johannes; Fries, Manfred; Moritz, Tassilo; Michaelis, Alexander
ABSTRACT: Additive Manufacturing is experiencing an upswing in many sectors of industry for a broad variety of materials. Processes are mainly developed for polymers and metals. For ceramics, hardmetals and especially cermets there are only a few additive processes suitable. The powder-based technique Binder-Jetting is one of these suitable processes with high productivity and relatively low green density. Within this study, TiCN-based cermets are printed by Binder-Jetting for the first time. The complexity of influences of the morphology and composition of cermet powders are discussed in regard to bulk density and material properties of printed and sintered parts. Studied TiCN-based cermet compositions represent different Ni and Mo2 C contents. Main points of this investigation are further the adjustment of ratio of the raw materials for good sintering behaviour and their influence on the microstructures and as a function of varied sintering temperatures.